PENGARUH CITRA MEREK, DESAIN PRODUK, DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA PRODUK PERSEBAYA STORE DI SURABAYA - Khoirul, Muhammad; Maduwinarti, Ayun; Pujianto, Agung (Jurnal Dinamika Administrasi Bisnis, 2020)
Nowadays, Indonesian soccer in the modern era has begun to move forward into a large industry. Persebaya Surabaya is also known as one of the biggest clubs in Indonesia with the enthusiasm of its supporters. Until finally Persebaya succeeded in opening "Persebaya Store" as a business entity that specializes in selling Persebaya Marchandise Surabaya. The author conducts research with the title "Effect of Brand Image, Product Design, and Product Quality on the purchasing decisions of Persebaya Store products in Surabaya" in order to find out how much influence the brand image, product design, and quality of persebaya store products in consumer purchasing decisions.This research uses puposive sampling technique to determine the number of respondents as much as 96 people. The analysis used in this study is Multiple Linear Regression Analysis. The stages before a regression analysis is carried out by conducting a validity and reliability test, then a classical assumption test is performed. After a regression analysis a partial test (t test), and the coefficient of determination test (R2), and simultaneous significance test (statistical test) f).The results of regression analysis in this study indicate that brand image, product design, and product quality have a positive influence on purchasing decisions with the equation. The The results of the analysis using the t test show that brand image, product design, and product quality have a significant influence individually on purchasing decisions.  Keywords: Brand Image, Product Design, Product Quality.